2019
DOI: 10.1111/ggi.13715
|View full text |Cite
|
Sign up to set email alerts
|

Association between decrease in frequency of going out and oral function in older adults living in major urban areas

Abstract: Aim To examine the association between a decrease in the frequency of going out and oral function in independent older adults living in the urban area of Tokyo. Methods The participants analyzed were 785 older adults from the “Takashimadaira Study” (344 men and 441 women, age 77.0 ± 4.6 years). This study investigated the following items: decrease in frequency of going out; basic characteristics (sex, age); physical factors, such as oral function (difficulty chewing, difficulty swallowing, dry mouth); body pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 24 publications
1
37
0
2
Order By: Relevance
“…23 Besides difficulties in eating, tooth loss without replacement can affect social aspects of daily living, such as embarrassment when smiling, laughing or showing their teeth, and speech problems. 24 Therefore, another potential explanation for the observed findings might rely on a moderation role of dental rehabilitation on the previously reported impact of tooth loss on depression 25 and social isolation, 26 which have been associated with cognitive decline. 27 Finally, it has been suggested that masticatory performance might be associated with brain activity and cerebral blood flow.…”
Section: Discussionmentioning
confidence: 87%
“…23 Besides difficulties in eating, tooth loss without replacement can affect social aspects of daily living, such as embarrassment when smiling, laughing or showing their teeth, and speech problems. 24 Therefore, another potential explanation for the observed findings might rely on a moderation role of dental rehabilitation on the previously reported impact of tooth loss on depression 25 and social isolation, 26 which have been associated with cognitive decline. 27 Finally, it has been suggested that masticatory performance might be associated with brain activity and cerebral blood flow.…”
Section: Discussionmentioning
confidence: 87%
“…Poor tongue movement makes it difficult to speak and may be associated with stress-induced weakness. Of those over 70 years of age, the group with a reduced frequency of going out had higher subjective difficulty in mastication than the group with no reduction in the frequency of going out [44]. Poor tongue movement may have affected withdrawal.…”
Section: Discussionmentioning
confidence: 94%
“…Social isolation accompanying loneliness triggers depressive symptoms, subjective memory decline, and the onset of dementia [ 11 , 44 ]. In addition, the lack of stimulus from oral conversation and verbal communication reduces the cross-talk between the mouth and brain, further resulting in deteriorated oral function (e.g., impaired chewing ability, salivation, and tongue pressure), loss of appetite, worsening depressive symptoms, and progressive cognitive complaints [ 45 47 ]. Subsequently, malnutrition occurs, which accelerates the vicious cycle of disability and mortality [ 11 ].…”
Section: Discussionmentioning
confidence: 99%